2016
DOI: 10.1038/srep26672
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of 3D laser-based anthropometry and comparison with classical anthropometry

Abstract: Anthropometric quantities are widely used in epidemiologic research as possible confounders, risk factors, or outcomes. 3D laser-based body scans (BS) allow evaluation of dozens of quantities in short time with minimal physical contact between observers and probands. The aim of this study was to compare BS with classical manual anthropometric (CA) assessments with respect to feasibility, reliability, and validity. We performed a study on 108 individuals with multiple measurements of BS and CA to estimate intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 29 publications
1
74
1
4
Order By: Relevance
“…In contrast to the earlier research and technical documents [27] that represents the technology as having a single answer of reliable to ± , the reality is that 3D Body Scanning's reliability is relative to the measurement being taken and the application it is being applied to. Although previous research [4], [12], [15] has asserted that the reliability of 3D Body Scanning measurements are comparable to that of manual measuring methods. Assuming correct manual measurement techniques are taken, they may extract measurements to a reliability of between ±3 up to ±25 [14] and in some cases these may not be the largest recorded difference during the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the earlier research and technical documents [27] that represents the technology as having a single answer of reliable to ± , the reality is that 3D Body Scanning's reliability is relative to the measurement being taken and the application it is being applied to. Although previous research [4], [12], [15] has asserted that the reliability of 3D Body Scanning measurements are comparable to that of manual measuring methods. Assuming correct manual measurement techniques are taken, they may extract measurements to a reliability of between ±3 up to ±25 [14] and in some cases these may not be the largest recorded difference during the process.…”
Section: Discussionmentioning
confidence: 99%
“…This is emphasised by the exceptional work of Gordon et al [14, p. 323] who stated that "scan-generated measurements tend to be significantly larger than those obtained by manual measurement". Further exploration of this issue was investigated in the ground-breaking work of Kuehnapfel et al [15] who demonstrated through inter-and inter-rater investigation that 3D Body Scanning is equivalent traditional manual measurements in feasibility, reliability, and validity. However, only limited number of body measurements were included in the sample, and the results were not compared against industrial use Proceedings of 3DBODY.TECH 2017 8th International Conference and Exhibition on 3D Body Scanning and Processing Technologies, Montreal, Canada, 11-12 Oct. 2017 allowances and this have limited context to practical application.…”
Section: Introductionmentioning
confidence: 99%
“…These measurement data can also be stored on computer system and retrieved whenever required (Treleaven & Wells 2007). Apart from that, physical contact between the practitioners and the subjects can be minimized (Kuehnapfel et al 2016). One of the important features of 3D body scanner is to produce 3D images of human body which cannot be obtained through manual measurement techniques.…”
Section: Introductionmentioning
confidence: 99%
“…But, BMI does not differentiate on body fat distribution (Wu et al 2014). Thus, it is really important to utilize proper methods in obesity assessment to avoid from neglecting the individuals who has the tendency to develop abdominal obesity even though they have normal BMI. A few researchers have reported that, anthropometric measurements can be used as important indicator for obesity assessment (Fryar et al 2012;Kuehnapfel et al 2016). Anhropometric data of body circumferences such as waist circumference (WC), hip circumference (HC) and waist to hip ratio (WHR) are currently been used as simple tools for evaluating the health status, disease risk and to estimate body fat distribution (Fryar et al 2012;Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Beside widespread commercial applications like apparel design and ergonomics [1,2], body scanning is increasingly utilized in medial context, e.g. for cosmetic and reconstructive surgery [3,4], and recently in medical and health research to study anthropometry of hundreds to thousands of participants in large cohort studies with high accuracy [5,6]. These new and amended data are expected to improve the diagnostics of many diseases, however, current applications usually don't consider the whole information provided by the set of body measures and, instead, use only a small part of them to estimate simple body indices such as body mass index (BMI) or waist-to-hip circumference ratio (WtH) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%